ANALYSIS OF FACTORS OF PATIENT COMPLIANCE WITH MULTI-VISIT ROOT CANAL TREATMENT IN KUPANG CITY - Ratih Variani; Applonia Leu Obi; M. Ibraar Ayatullah (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2022)
Abstract [Times New Roman 10] Background: Dental caries that reached the pulp required root canal treatment. Non-compliance in undergoing treatment in the field of conservation and endodontic teeth can cause treatment failure, which results in the treatment having to be repeated. Factors that affected a person's compliance include knowledge, education, income, employment, motivation, perception, satisfaction, and treatment costs. The purpose of the study: to determine the factors of patient compliance with multi-visit root canal treatment in Kupang City. Research method: An analytic study with a cross-sectional approach. The sample of this study used accidental sampling, namely patients who received dental root canal treatment at dental practices throughout the city of Kupang with a total sample of 40 people. The Spearman correlation test was used to determine the factors of patient compliance with multi visit root canal treatment in Kupang City. The results: There was a significant relationship between income (p=0.006), education (p=0.010), knowledge (p=0.003), motivation (p=0.000), perception (p=0.001), satisfaction (p=0.000), and cost of care (p=0.007) with patient compliance. While the occupational factor (p=0.843) had no relationship with patient compliance. The dominant factor was the cost of root canal treatment. The strength of the relationship between variables was -0.418, meaning that the relationship was sufficient and negative, which meant that the lower the cost of treatment, the higher consumer compliance. Conclusion: There was a relationship between the factors of knowledge, income, education, motivation, perception, satisfaction, and cost of care with patient compliance. For the work factor, there was no relationship. Meanwhile, the dominant factor was the cost of root canal treatment.